KUALITAS KIMIA DAGING SE’I YANG DIBERI EKSTRAK ANGKAK DAN LAMA PENYIMPANAN BERBEDA CHEMICAL QUALITY OF SE’I (Rotenesse Smoked Meat) TREATED WITH RED YEAST RICE EXTRACT IN DIFFERENT STORAGE TIMES - Bastari Sabtu; Ni Putu Febri Suryatni (Universitas Nusa Cendana, 2015)
The study aimed to evaluate the chemical quality of se’i treated with red yeast rice extract in different storage times. Factorial of completely randomized design was used in the study. The two factors were red yeast rice extract levels and storage times. The red yeast rice extract levels consisted of: 0% (control), 1%, 1.5%, 2% and 2.5% as I factor; and the storage times were: 3, 5, 7 and 9 days. Each combinations of those two factors had 3 replicates. The variables evaluated were: water, protein and fat contents of the se’i. Data were analyzed using analysis of variance with SPSS 17 version. The result showed that there was no interaction between red yeast extract and storage time on water and protein contents but there was significanlyt effect on fat content. The conclusion drawn is that se’i treated with 2.5% red yeast rice extract stored for 9 days reduces level of fat contents of se’i. Using of 2% red yeast rice extract perform similar results with control. It is better to reduce the storage time to be 7 days by evaluating other additional se’i quality variables. ABSTRAK Penelitian bertujuan untuk mengkaji kualitas kimia daging sei yang diberi ekstrak angkak merah dan lama simpan berbeda. Rancangan yang digunakan adalah rancangan acak lengkap pola faktorial. Perlakuan terdiri dari 2 faktor, faktor pertama adalah pemberian ekstak angkak, 0% (Kontrol), 1%, 1.5%, 2% dan 2.5% dan faktor kedua adalah lama simpan, 3 hari, 5 hari, 7 hari dan 9 hari. Kombinasi perlakuan diulang sebanyak 3 kali. Parameter yang diukur adalah kadar air, protein dan lemak daging se'i. Data dianalisis menggunakan Analisis Variansi dengan program SPSS versi 17. Hasil penelitian menunjukkan tidak adanya interaksi antara pemberian ekstrak angkak dengan lama simpan terhadap kadar air, protein dan adanya interaksi antara pemberian ekstrak angkak dan lama simpan terhadap kadar lemak. Kesimpulan, Pemberian ekstrak angkak merah sampai pada level 2,5% selama penyimpanan 9 hari ada kecenderungan menurunkan kadar lemak daging se’i. Pada level pemberian 2% menghasilkan kadar air, protein dan lemak daging se’i yang relatif sama dengan kontrol. Sebaiknya, penyimpananan lebih dipersingkat kurang dari 7 hari dengan melihat kondisi fisik daging se’i lainnya.